Satisfação com o tratamento ortodôntico: tradução, adaptação transcultural e validação de um instrumento para a Língua Portuguesa do Brasil - Renata Negreiros Alvarenga (2020)
There is a scarcity of validated instruments for assessing satisfaction with services, where orthodontic treatment is provided. In the Brazilian Portuguese language, there is no validated questionnaire that addresses this outcome. This dissertation aimed to translate into the Brazilian Portuguese language, cross-culturally adapt and validate an instrument for the assessment of satisfaction in Orthodontics. The instrument assesses the satisfaction of parents/guardians of individuals under the age of 18 regarding the orthodontic treatment of their children. The Federal University of Minas Gerais (UFMG) Ethics Research Committee has approved this study (protocol 06898519.4.0000.5149), and the phases of this study followed international guidelines for translation, cross-cultural adaptation and validation of instruments for the assessment of health outcomes, which are: translation of the instrument from English to Brazilian Portuguese, revision of the translations by a multidisciplinary committee composed of Brazilian specialists, back-translation into English, pre-test and evaluation of the validity and reliability of the Portuguese version obtained. The questionnaire consists of 25 questions, distributed across 3 subscales (process, psychosocial effect and outcome). The sample consisted of 83 parents/caregivers of children/adolescents under 18 years of age who completed orthodontic treatment. Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS) software, and descriptive statistics were performed. Internal consistency and stability were calculated using the Cronbach’s α coefficient and the intraclass correlation coefficient (ICC), respectively. The convergent construct validity was tested using the Pearson's coefficient through the association between pairs of questionnaire subscales. The discriminant construct validity was determined by means of the comparison between male and female parents/caregivers who answered the questionnaire regarding the subscale scores and the total questionnaire score. From the 83 children/adolescents who participated in the study, 41 (49.4%) were boys and 42 (50.6%) were girls. The mean age of children/adolescents was of 13.0 years (±3.07). In the total score of the questionnaire and in the scores of the three subscales, an acceptable percentage (15% or lower) of participants achieved the maximum score. In the total questionnaire score and in the three subscales, no participant achieved the minimum score. Regarding internal consistency, the value of the Cronbach's α coefficient for the total score of the questionnaire was of 0.72. For the subscales, the values ranged from 0.68 to 0.75. Regarding test-retest reliability, the ICC value for the total score of the questionnaire was 0.71, indicating good correlation. For the subscales, the values ranged from 0.68 to 0.72. For construct validity, the total score of the questionnaire presented large Pearson correlation coefficient (>0.50) with the three subscales. For discriminant validity, female parents/caregivers had significantly higher scores in the psychosocial effect subscale (p=0.013) and in the outcome subscale (p=0.037) compared to male parents/caregivers. The version obtained in this study proved to be valid and reliable for use in the Brazilian population.